2007
DOI: 10.1128/aem.02067-06
|View full text |Cite
|
Sign up to set email alerts
|

Epilithic Cyanobacterial Communities of a Marine Tropical Beach Rock (Heron Island, Great Barrier Reef): Diversity and Diazotrophy

Abstract: The diversity and nitrogenase activity of epilithic marine microbes in a Holocene beach rock (Heron Island, Great Barrier Reef, Australia) with a proposed biological calcification "microbialite" origin were examined. Partial 16S rRNA gene sequences from the dominant mat (a coherent and layered pink-pigmented community spread over the beach rock) and biofilms (nonstratified, differently pigmented microbial communities of small shallow depressions) were retrieved using denaturing gradient gel electrophoresis (DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…In the central part of the Lake Maggiore, two specimens revealed the presence of several cyanobacteria mostly belonging to Oscillatoriales. The blooms were mainly due to Pseudanabaena spp., an unusual condition in Lake Maggiore, as this taxon commonly blooms in eutrophic water bodies (Mayer et al, 1997;Zwart et al, 2005); nonetheless, its characteristics are poorly investigated (Acinias et al, 2009) even widely distributed as it occurs in diverse aquatic as well as in benthic environments (Castenholz et al, 2001;Zwart et al, 2005;Diez et al, 2007). In the two samples collected in the central lake station, several species belonging to Oscillatoriales have contributed to the algal bloom, among which Pseudanabaena dominated, both in terms of density (68.6 and 57.0%, respectively) and biomass (47.2 and 52.6%).…”
Section: Bloom Maps and In Situ Analysismentioning
confidence: 99%
“…In the central part of the Lake Maggiore, two specimens revealed the presence of several cyanobacteria mostly belonging to Oscillatoriales. The blooms were mainly due to Pseudanabaena spp., an unusual condition in Lake Maggiore, as this taxon commonly blooms in eutrophic water bodies (Mayer et al, 1997;Zwart et al, 2005); nonetheless, its characteristics are poorly investigated (Acinias et al, 2009) even widely distributed as it occurs in diverse aquatic as well as in benthic environments (Castenholz et al, 2001;Zwart et al, 2005;Diez et al, 2007). In the two samples collected in the central lake station, several species belonging to Oscillatoriales have contributed to the algal bloom, among which Pseudanabaena dominated, both in terms of density (68.6 and 57.0%, respectively) and biomass (47.2 and 52.6%).…”
Section: Bloom Maps and In Situ Analysismentioning
confidence: 99%
“…DGGE based 16S rRNA analyses of microbial diversity revealed that the pink and the black biofilms were the 311 most genetically distinct of all the beachrock communities on Heron Island (Diez et al 2007). Of particular 312 interest, the black biofilm is dominated by heterocystous diazotrophs, whereas non-heterocystous cyanobacteria 313 dominate the pink biofilm (Diez et al 2007).…”
mentioning
confidence: 99%
“…Like all intertidal 51 environments, the beachrock habitat is an environment of extreme conditions, being exposed to strong 52 insolation, extreme temperatures, periodic desiccation and concurrent hypersalinity stress in ponded regions of 53 the rock platform during low tide and air exposure. Such intertidal habitats are extremely diverse, as they 54 provide a steep environmental gradient over a small spatial scale (Davison and Pearson 1996), exhibiting 55 distinct transitions of diverse epilithic and endolithic microbial communities (Diez et al 2007). …”
mentioning
confidence: 99%
See 2 more Smart Citations